A Systematic Review of Risk-Taking Behavior Among Indonesian Military Personnel - Selyo Febrio Xavier; IGAA Noviekayati; Suhadianto Suhadianto (jfpublisher, 2026)
Risk-taking behavior among military personnel is an important issue in military psychology because soldiers are frequently required to make decisions under conditions of uncertainty, pressure, and potential danger. However, literature specifically examining risk-taking behavior among Indonesian National Armed Forces (TNI) personnel remains limited, with existing studies focusing more on resilience, stress, and general psychological well-being. This study aimed to synthesize recent findings on the factors influencing risk-taking behavior among military personnel, with particular relevance to the TNI context, through a systematic literature review approach. The study analyzed 10 relevant articles published between 2020 and 2025, identified through searches in Scopus and Google Scholar. The findings indicate that risk-taking behavior is influenced by multidimensional factors, including physiological factors such as sleep quality and energy balance, psychological factors such as impulsivity, optimism bias, and professional identity, and operational factors such as combat exposure. Social support was also found to play a protective role by reducing the tendency toward maladaptive risk-taking. These findings provide a broader understanding of the dynamics of risk-taking behavior among military personnel and highlight the importance of integrated training and psychological support strategies to improve decision-making in high-risk military environments.